Inclusive VR through Inclusive Co-Design with Neurodiverse Learners - Dahlstrom-Hakki, Ibrahim; Edwards, Teon; Larsen, Jamie; Alstad, Zachary; Belton, Gerald; Lougen, Daniel; Santana, Daniel (2021 7th International Conference of the Immersive Learning Research Network (iLRN), 2021)
This paper reports on a fully inclusive co-design process of an informal VR science game intended to be accessible to a broad range of learners. The co-design embraces the 'nothing about us without' us movement by ensuring that stakeholder voices have a prominent role throughout the design process. In the project described in this paper, professional designers and researchers work with a team of neurodiverse stakeholders as peer members of the design team. The design process is described, and the findings based on feedback from all co-design participants is reported. Recommendations for others in the field are provided to help guide those interested in implementing an effective and inclusive co-design process.